Efficacy and Safety of a Unani Pharmacopeial Powder Formulation and Sharbat banafsha in Women with Uncomplicated Urinary Tract Infection: A Pilot Self-Control Clinical Trial - Sultana, Arshiya; Rahman, Khaleequr; Khaleeq, Khadija (Current Nutrition & Food Science, 2025)
BackgroundAntimicrobial resistance is a growing global concern, highlighting the urgent need for effective non-antibiotic alternatives to treat urinary tract infections. Effortlessly blending traditional Unani knowledge with modern scientific evaluation, this study highlights the potential of Unani formulations in managing uncomplicated UTIs. This study's findings underscore the importance of exploring and bridging the gap between Unani medicine and evidence-based practices. This study investigates the efficacy and safety of an Unani Pharmacopeial powder formulation and Sharbat Banafsha in treating women with uncomplicated urinary tract infections (UTI).Materials and MethodsThe pre and post-test pilot self-control clinical study involved 13 participants with uUTI who received 3.5 g powder Unani formulation comprising Lagenaria siceraria (Molina) Standl, Malva sylvestris L., Cucumis sativus L. and Cucumis melo L., Portulaca oleracea L., and Adiantum capillus L. with Sharbat Banafsha (syrup of Viola odorata L.) 25 ml twice daily for 8 days. The primary outcomes were assessed using the urinary tract infection symptoms assessment (UTISA) questionnaire, while secondary outcomes included urine culture and sensitivity, as well as health-related quality of life (HRQoL) assessment using the SF-12 health survey. The data was analyzed, and p<0.05 was considered significant.ResultsThe UTISA total score from 15.69 ± 2.18 was reduced to 4.00 ± 5.07 on day 9 with a significance difference (p < 0.001). On day 14, 84.61% of the population had negative cultures. The total SF-12, PCS, and MCS scores showed significant differences from Day 0 to 60 (p>0.05). No adverse effects were reported in both groups. HPLC analysis confirmed the presence of the plant metabolite luteolin in both the powder and syrup.ConclusionThe data explores the effectiveness of Unani formulations for bacterial urinary tract infections (UTI), showing no adverse effects while also improving the HRQoL of women. These herbal products contain luteolin, a bioactive molecule with antimicrobial properties.Clinical Trial Registration NumberCTRI/2020/02/023404 dated 17/02/2020.
Keywords: uncomplicated urinary tract infection (UTI)